Asia‐Pacific Integration with China versus the United States: Examining Trade Patterns under Heterogeneous Agricultural Sectors. (21st July 2015) - Heerman, Kari E. R.; Arita, Shawn; Gopinath, Munisamy
Abstract : This article examines bilateral trade patterns in the Asia‐Pacific using a new model in which comparative advantage within the agricultural sector is linked to agro‐ecological characteristics, and trade costs are product‐specific. Bilateral market share is a function of productivity and trade costs. However, countries with similar land and climate characteristics systematically have high productivity in similar products making them disproportionately sensitive to changes in each other's trade costs. We use a random coefficients logit model to estimate a parametric distribution of comparative advantage and trade costs across products and calculate regional trade liberalization elasticities for each exporter in each import market. Unlike most existing models, the value of the elasticity depends on the degree to which liberalization includes competitors with similar comparative advantage within the agricultural sector. We find disproportionately larger trade elasticities under China‐led liberalization relative to U.S.‐led liberalization among close U.S. competitors compared to countries whose agricultural products are unlikely to compete head‐to‐head with U.S. exports. For the United States, we find that the "lost opportunity" cost of exclusion from regional liberalization is increasing in the extent to which its close competitors gain new access.